CART: Cell-free and Concentrated Ascites Reinfusion Therapy against malignancy-related ascites. Issue 5 (October 2017) - Ito, Tetsuya; Hanafusa, Norio
Abstract: A standard strategy against ascites, a common symptom observed in cirrhotic and cancer patients, includes restriction of sodium intake and use of a diuretic. Paracentesis is a widely applied method against refractory ascites that do not react to such treatment. However, emerging fatigue and hemodynamic instability are possibly attributable to a loss of protein included in ascites. Cell-free and Concentrated Ascites Reinfusion Therapy (CART) is also applied against refractory ascites. CART comprises three processes. After ascites is first filtered to remove cell components, it is concentrated to reduce its volume. Fluid obtained through these processes, including useful proteins such as albumin and globulin, is finally reinfused intravenously. CART was reported first in the 1970s. Since then, it has been applied mainly against cirrhotic ascites with a thinner cell component. Now, its indication is expanding to include malignancy-related ascites. Additionally, CART can be applied safely against malignancy-related ascites. Its favorable effects on control of patients' symptoms are anticipated, especially on fatigue. Although related evidence has not been established, CART can be anticipated for use as a strategy against refractory ascites.